2017
DOI: 10.5455/apd.256532
|View full text |Cite
|
Sign up to set email alerts
|

The relationships between low grade inflammation, demographic and clinical characteristics in patients with obsessive compulsive disorder

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Mean CRP in the OCD group exceeded this level despite no comorbid depression (mild symptoms were present in some); this relationship was also independent of BMI, age or sex. To date, only one cross‐sectional study has examined levels of CRP levels in OCD patients, which also revealed elevations in patients (13). Despite the independent associations of OCD with CRP and the gut microbiome profile, respectively, CRP levels and the observed taxa differences were not correlated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mean CRP in the OCD group exceeded this level despite no comorbid depression (mild symptoms were present in some); this relationship was also independent of BMI, age or sex. To date, only one cross‐sectional study has examined levels of CRP levels in OCD patients, which also revealed elevations in patients (13). Despite the independent associations of OCD with CRP and the gut microbiome profile, respectively, CRP levels and the observed taxa differences were not correlated.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond this, current theories describing the pathophysiological mechanism of OCD may also be modulated by the gut microbiome (11). In particular, inflammation is a leading theory linking psychiatric conditions and the gut microbiome, and given that there is some evidence of immune dysregulation in OCD (12,13), this line of research should be pursued.…”
Section: Introductionmentioning
confidence: 99%